Pengembangan Media Pembelajaran Berbentuk Multimedia Interaktif pada Materi Bangun Ruang Siswa Kelas VI Sekolah Dasar - Agus Satria Daulay (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
The progress and development of technology is increasingly rapid, making all compete to adapt to technology, one of which is the world of education and curriculum. For curriculum simplification, only the main material in learning activities needs to be conveyed, while for training can be independently or through application media. This research aims to create interactive multimedia-based learning media on building space material for grade VI elementary school students. This media can make it easier for students to understand the material to be conveyed and be able to adapt to technology, namely multimedia, this study uses research and development methods that are aligned with the curriculum used at school. Features in the multimedia include objectives and materials, as well as learning videos, and also evaluation. The product can be accessed using a smartphone.